Characteristics of Chronic Maxillary Sinusitis in Patients With a History of Long-term Bisphosphonate Use. Issue 5 (September 2019) - Hwang, Chi Sang; Lee, Chunui; Chae, Hee Sung; Han, Chun; Yang, Hyun Woo; Lee, Young Sub; Park, Dong-Joon
Background: Bisphosphonates are widely used as bone stabilizers, which can cause major side effects including bisphosphonate-related osteonecrosis of the jaw (BRONJ) that occurs more frequently in the mandible. Consequently, there is a need for a detailed investigation of BRONJ of the maxilla and, in particular, of involvement of the maxillary sinus. Objective: Our aim was to evaluate the characteristic radiologic and clinical manifestations in patients with maxillary sinusitis and a history of long-term bisphosphonate use. Methods: Between January 2015 and July 2018, 55 patients with symptoms consistent with chronic rhinosinusitis who underwent a paranasal sinus computed tomography (CT) and had a history of >12 months of bisphosphonate therapy were included in the analysis. Results: Radiologically and clinically evident chronic rhinosinusitis was noted in 24 of the 55 patients, of whom more than half (14/24, 58.3%) had BRONJ. The CT studies demonstrated that the maxillary sinus was involved in all 24 patients, characterized by unilateral involvement (70.8%) and bony remodeling in the posterior maxillary region (90.5%). The evidence of osteitis on CT and/or single-photon emission CT was observed in the majority of cases (19/21, 90.5%) and 12 patients (50.0%) had oroantral fistula. However, there were no differences in the clinical appearance of the diseases with respect to the radiologic aspects. Conclusions: Besides its well-known effects on the mandible, long-term bisphosphonate use can also affect the maxillary sinus, with typical clinical and radiological manifestations.